Bioequivalence of 2 Aripiprazole Orally Disintegrating Tablets in Healthy Chinese Volunteers Under Fasting and Fed Conditions. Issue 8 (8th June 2021) - Xiang, Jin; Xu, Nan; Wang, Xueyan; LI, Songfan; Yu, Qin; Liang, Maozhi; Nan, Feng; Shu, Shiqing; Yan, Rui; Zhu, Yuqi; Liao, Linchuan
Abstract: To assess the bioequivalence of 2 formulations of aripiprazole orally disintegrating tablets and to monitor their safety and tolerability in Chinese subjects, a single‐site, open‐label, randomized, 2‐preparation, single‐dose, 2‐period crossover design was conducted. All 60 subjects were randomly divided into the fasting group and the fed group. Blood samples were collected at scheduled times after a single oral dose of orodispersible tablets containing 10 mg of aripiprazole. In the fasting state, the geometric mean ratios (90% confidence intervals [CIs]) of the test/reference formulation were 92.22%‐100.20% for the area under the concentration‐time curve (AUC) from time zero to the last measured concentration (AUC0‐t ), 91.73%‐100.14% for the AUC from administration to infinite time (AUC0‐∞ ), and 98.52%‐112.52% for the maximum plasma concentration (Cmax ). In the fed state, AUC0‐t, AUC0‐∞, and Cmax were 92.23%‐100.20%, 91.73%‐100.14%, and 95.91%‐105.13%, respectively. The 90%CIs of the test/reference AUC ratio and Cmax ratio were within the acceptance range of 80.00%‐125.00% for bioequivalence. Neither the maximum peak plasma concentration (tmax ) nor the terminal elimination half‐life (t1/2 ) showed any significant difference. No serious adverse events) were encountered during the study. The test and reference formulations were bioequivalent under both fasting and fed conditions and were found to be safe and tolerated.